An Energy Approach for Determining the Effective Mechanical Properties of Particulate-Reinforced Metal Matrix Composites - Surasak Suranuntchai, (Agriculture and Natural Resources, 2002)
A significant challenge to the determination of particulate-reinforced metal matrix composites (PRMMCs)’s effective mechanical properties is the lack of conveniently approximating techniques. With this reason, an energy approach has been employed to develop the simple relationships between the mechanical properties, such as the modulus of elasticity and the yield stress, of PRMMCs and the corresponding properties of unreinforced matrix materials together with volume fractions of reinforcement. Thus, given the necessary mechanical properties of a matrix material and the volume fraction of reinforcing particles, such the PRMMC’s effective properties can be easily predicted. However, after applying the relationships adopted to test with an aluminium matrix alloy, AA6061, reinforced by the silicon carbide (SiC) particulate over a range of einforcement volume fractions, i.e. from 10% to 40%, the predicted valuesshow a poor approximation when compared with the experimental data. For the case of modulus of elasticity, they tend to give rise to more discrepancies with increasing volume fractions of reinforcement. Similar situations are also observed in case of yield stress predictions, especially when the volume fraction values beyond 20%. Due to the rigid-perfectly plastic behavior assumption of the composite materials considered, the variation of yield stresses determined by such an energy method provide the overestimation to the data those obtained from experiments.